DEVELOPMENT OF INSTANT SHAKE MIX FROM SPROUTED RAGI POWDER - A.S. SREELAKSHMI; C. L. SHARON; S.T. PANJIKKARAN; K. T. SUMAN; P. S. LAKSHMY; ATHIRA RAJ; DELGI JOSEPH, C. (The Journal of Research ANGRAU, 2024)
Ragi or finger millet (Eleusine coracana L.) is a common millet grown in several regions of India.The sprouted ragi powder was incorporated in different proportions ranging from 80 percent to 40 per cent,along with skimmed milk powder and nuts. The best treatment was obtained through sensory evaluation using a scorecard with a nine-point hedonic scale. Based on the organoleptic evaluation, the shake mix prepared with 50 per centsprouted ragi powder and 45 percent skimmed milk powder had a highest mean score of 8.36 for overall acceptability other than control (100% skimmed milk powder).The selected instant shake mix was subjected to chemical analysis and was observed to have energy (383.84 Kcals), carbohydrate (72.66 g per 100 g), protein (19.43 g per 100 g), fat (1.72 g per 100 g), calcium (1450 mg per 100 g) and iron (12.96 milli gram per 100 gram). A highly acceptable, nutritionally superior, and shelf-stable instant shake mix can be successfully developed using sprouted ragi powder.